Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
solve the differential equation?
dy/dx+at=e^x a not equal to -1
y not t I mean ay not at
1 Answer
- hfshawLv 74 years ago
dy/dx + a*y = exp(x), a ≠ -1
This is a first-order linear equation that we can solve using an intgrating factor.
For equations of the form:
dy/dx + a(x)*y = b(x),
the integrating factor, p(x) is given by:
p(x) = exp(INTEGRAL of {a(x) dx}) [we don't have to worry about the constant of integration at this step because it turns out it can always be combined with the constant arising from the next integration]
and the solution is given by:
y(x) = (1/p(x))*INTEGRAL of {p(x) * b(x) dx}
In this case,
p(x) = exp(INTEGRAL of {a dx}) = exp(a*x)
So:
y(x) = exp(-a*x)*INTEGRAL of {exp(a*x) * exp(x) dx}
y(x) = exp(-a*x)*INTEGRAL of {exp(a*x + x) dx}
y(x) = exp(-a*x)*INTEGRAL of {exp((a+1)*x) dx}
y(x) = exp(-a*x)*[((1/(a+1))*exp((a+1)*x) + c]
where c is the constant of integration.
y(x) = exp(x)/(a+1) + c*exp(-a*x)